Axial load distribution and self-loosening behavior of bolted joints subjected to torsional excitation. (January 2021) - Liu, Xuetong; Mi, Xue; Liu, Jianhua; Long, Laohu; Cai, Zhenbing; Mo, Jiliang; Peng, Jinfang; Zhu, Minhao
Highlights: A finite element method of building up different threads was presented originally. The effects on axial load distribution of bolted joints were studied. The effects on loosening behavior of bolted joints were studied. Abstract: Axial load distribution and self-loosening behavior of bolted joints were numerically studied in this work. Finite element (FE) models with fine mesh threads were generated by analyzing the clearance of different thread fit qualities and thread profiles of MJ and Spiralock internal threads. By changing the thread clearance value, thread profile, engagement length, pitch value, and friction coefficients, their effects on axial load distribution, loosening behavior, and the dynamic response of bolted joints were explored with accurate three-dimensional FE models. In addition, experiments were conducted to investigate the dynamic response of bolted structures. Numerical results agreed with the theoretical results. For varying friction coefficients between the contact threads and between the bolt head and the bearing surfaces, the clamping force of bolted joints excited by torsional load changed in three cases: continuously decreasing, initially decreasing and then remaining constant, and initially decreasing and then fluctuating. Agreement was achieved by comparing between hysteresis loops generated by numerical and experimental methods.